2017
DOI: 10.15537/smj.2017.8.18084
|View full text |Cite
|
Sign up to set email alerts
|

The use of oral and maxillofacial pathology services by general pathologists and their attitude towards it in Saudi Arabia

Abstract: Objectives:To investigate the awareness and usage of oral and maxillofacial pathology (OMFP) subspecialty services among pathologists in Saudi Arabia.Methods:In this cross-sectional study, we conducted an electronic questionnaire survey of pathologists in all regions of Saudi Arabia. The study was conducted between July 2015 and August 2016. The questionnaire comprised 19 questions to evaluate the knowledge of pathologists regarding microscopic OMFP and their perceptions towards this subspecialty.Results:Most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…[ 4 ] On the other hand, Binmadi and Almazrooa reported in their study that only 32.4% of the pathologists were prepared to consider hiring an OMFP specialist at their department. [ 3 ] Our survey also showed only 30% referrals to OMFP specialists, which was also the case in a survey conducted by Binmadi NO. Barret and Speight have reported a slightly larger number of referrals in their study.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…[ 4 ] On the other hand, Binmadi and Almazrooa reported in their study that only 32.4% of the pathologists were prepared to consider hiring an OMFP specialist at their department. [ 3 ] Our survey also showed only 30% referrals to OMFP specialists, which was also the case in a survey conducted by Binmadi NO. Barret and Speight have reported a slightly larger number of referrals in their study.…”
Section: Discussionsupporting
confidence: 80%
“…Mudaliar et al in India (Mumbai), on the other hand, have reported lower percentages for the same in their study. [ 3 4 5 ] These differences, as highlighted by studies, could be due to differences in the training methods and curriculum related to the specialty of oral pathology. Hence, generating interest among the students toward the specialty by implementing new ideas in the curriculum in a constructive manner is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence shows that these lesions usually progress slowly, and a spontaneous growth stop is usually another characteristic. 1,2 Affected patients are usually asymptomatic. However, symptoms might be reported in edentulous patients and cases when the lesion is huge.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note, that the reason that OMFS is the only recognized dental specialty by the ABHS is likely due to the lack of awareness of the need of OM and OP services. Moreover, despite an increasing demand for OP specialists, a recent study concluded that there is a low utilization of OP services in Saudi Arabia, even when general pathologists were aware of oral pathologists and the specialty ( Binmadi and Almazrooa, 2017 ).…”
mentioning
confidence: 99%